1991
DOI: 10.1017/s0022112091002422
|View full text |Cite
|
Sign up to set email alerts
|

Onset of convection in an anisotropic porous medium with oblique principal axes

Abstract: We investigate the onset of Rayleigh–Bénard convection in a horizontal porous layer with anisotropic permeability. The permeability is transversely isotropic, whereas the orientation of the longitudinal principal axes is arbitrary. This is sufficient to achieve qualitatively new flow patterns with a tilted plane of motion or tilted lateral cell walls. The critical Rayleigh number and wavenumber at marginal stability are calculated. There are two different types of convection cells (rolls): (i) the plane of mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 9 publications
4
49
0
1
Order By: Relevance
“…Qin and Kaloni [52] develop a non-linear energy stability analysis for thermal convection in an anisotropic porous solid when the permeability axes are orthogonal to the layer. Tyvand and Storesletten [53], however, considered an anisotropic permeability with axes inclined at an arbitrary angle to the convection layer and showed this could have a strong e ect on thermal convection behaviour. Storesletten [54] develops a similar analysis for an anisotropic thermal di usivity with axes non-orthogonal to the layer; the ÿndings here are also signiÿcantly di erent from the orthogonal case.…”
Section: Anisotropic Porous Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Qin and Kaloni [52] develop a non-linear energy stability analysis for thermal convection in an anisotropic porous solid when the permeability axes are orthogonal to the layer. Tyvand and Storesletten [53], however, considered an anisotropic permeability with axes inclined at an arbitrary angle to the convection layer and showed this could have a strong e ect on thermal convection behaviour. Storesletten [54] develops a similar analysis for an anisotropic thermal di usivity with axes non-orthogonal to the layer; the ÿndings here are also signiÿcantly di erent from the orthogonal case.…”
Section: Anisotropic Porous Mediamentioning
confidence: 99%
“…Storesletten [54] develops a similar analysis for an anisotropic thermal di usivity with axes non-orthogonal to the layer; the ÿndings here are also signiÿcantly di erent from the orthogonal case. Straughan and Walker [23] adopted the Tyvand and Storesletten [53] situation but allowed the density to be quadratic in temperature, i.e.…”
Section: Anisotropic Porous Mediamentioning
confidence: 99%
“…The orientation of the principal axes of K are assumed to be parallel to the sides of the domain. For the situation of an arbitrary orientation of coordinate axes, the reader is referred to Tyvand and Storesletten [25]. The dynamic £uid viscosity W is taken as a constant.…”
Section: Formulationmentioning
confidence: 99%
“…A few studies have also been concerned with the case when the principal axes of anisotropy of the porous structure are inclined with respect to the gravity force. For this situation, the onset of motion in a porous layer heated from below was predicted by Tyvand and Storesletten (1991) [12] and Zhang et al (1993) [13]. It was demonstrated that the influence of the anisotropy orientation considerably modifies the stability limit.…”
Section: Introductionmentioning
confidence: 92%